The diversity of the microbiome impacts chronic lymphocytic leukemia development in mice and humans - Faitová, Tereza; Coelho, Mariana; Cunha-Bang, Caspar da; Öztürk, Selcen; Cevirgen, Ece; Bork, Peer; Seiffert, Martina; Niemann, Carsten U. (Haematologica, 2024)
The gut microbiota plays a critical role in maintaining a healthy human body and its dysregulation is associated with various diseases. In this study, we investigated the influence of gut microbiome diversity on the development of chronic lymphocytic leukemia (CLL). Analysis of stool samples from 59 CLL patients revealed individual and heterogeneous microbiome compositions, but allowed for grouping of patients according to their microbiome diversity. Interestingly, CLL patients with lower microbiome diversity and an enrichment of bacteria linked to poor health suffered from a more advanced or aggressive form of CLL. In the Eµ-TCL1 mouse model of CLL, we observed a faster course of disease when mice were housed in high hygiene conditions. Shotgun DNA sequencing of fecal samples showed that this was associated with a lower microbiome diversity which was dominated by Mucispirillum and Parabacteroides genera in comparison to mice kept under lower hygiene conditions. In conclusion, we applied taxonomic microbiome analyses to demonstrate a link between gut microbiome diversity and the clinical course of CLL in humans, as well as the development of CLL in mice. Our novel data serve as a basis for further investigations to decipher the pathological and mechanistic role of intestinal microbiota in CLL development.